Serotype distribution and antibiotic susceptibility of invasive Streptococcus pneumoniae isolates in patients aged 50 years or older in Thailand - Somporn Srifuengfung (2018)
As the 13-valent pneumococcal conjugate vaccine (PCV13) has been approved for use in adults aged 50 y and older, we evaluated vaccine-serotype coverage rate in Thai adult patients with invasive pneumococcal infections before the vaccine was widely used. Of the 157 S. pneumoniae isolates from normal sterile sites during January 2005 to September 2012, 150 (95%) from blood, mean patients' age 69.6 (range 50-89) years, the overall serotype coverage by PCV13 was 58%. The vaccine covered 50%, 56%, 59%, and 68% of the invasive isolates from patients aged 50-59, 60-69, 70-79, and ≥80 y, respectively. The most common vaccine serotypes were 6B (17%), 19A (9%), 18C (5%), and 23F (4%). The susceptibility rates of penicillin and ceftriaxone were 95% and 96% for nonmeningitis criteria; and 46% and 92% for meningitis criteria, respectively. The susceptibilities to other antibiotics were: chloramphenicol 76%, clindamycin 80%, erythromycin 57%, levofloxacin 100%, ofloxacin 94%, tetracycline 39%, trimethoprim/sulfamethoxazole 37%, linezolid 99%, and vancomycin 100%, respectively. These data served as a reference for monitoring of vaccine serotype coverage with future increased vaccine utilization. © 2014 Landes Bioscience.